Effect of post-exfoliation treatments on mechanically exfoliated MoS2. (22nd February 2017) - Budania, P; Baine, P T; Montgomery, J H; McNeill, D W; Mitchell, S J N; Modreanu, M; Hurley, P K
Abstract: Post-exfoliation thermal annealing in air and ultrasonic treatments were carried out on mechanically exfoliated MoS2 flakes on oxidized silicon substrates. Ultra-sonication of MoS2 flakes on SiO2 without prior annealing results in almost complete removal of flakes, indicating weak interface bonding. The interface adhesion between MoS2 flakes and the substrate is significantly improved when the samples are annealed at 270 °C as the flakes remain strongly adhered to the substrate during subsequent ultrasonic treatment. We consider that improved adhesion is due to greater contact area between the flakes and the substrate due to effusion of trapped impurities during annealing. Annealing between 75 °C and 175 °C followed by ultrasonic treatment results in small MoS2 fragments on the samples due to breakage and/or partial removal of top layers. It also results in exposing residual adhesive traces on the sample which are caught between the flake and the substrate during repetitive folding of the Scotch ® tape during the initial exfoliation. An annealing temperature of 460 °C results in decomposition of MoS2 and formation of MoO3 . Optical microscopy, non-contact-mode atomic force microscopy (AFM) and Raman spectroscopy were used for identification of MoS2 fragments and residual traces left on the samples after the post-exfoliation treatments.